(untitled) (Homoeopathy for All, 2025)
The skin is the body’s largest organ, functioning as a protective shield. Natural response of the skin to repeated friction or pressure is hyperkeratosis, a process where the outer layer thickens due to excessive keratin production. This mechanism strengthens the skin against mechanical stress but, when excessive, leads to conditions like corns and calluses. The aim of this article is to understand the etiology, signs & symptoms of corns & calluses and role of homeopathy in cases of corns & calluses. Homeopathic system proves to help in such diseases as it follows holistic approach in which curing sick is more important rather than disease itself.